Novel Posttranslational Activation of the LYS2-Encoded α-Aminoadipate Reductase for Biosynthesis of Lysine and Site-Directed Mutational Analysis of Conserved Amino Acid Residues in the Activation Domain of Candida albicans - Guo, Shujuan (American Society for Microbiology, 2001)
The α-aminoadipate pathway for lysine biosynthesis is present only in fungi. The α-aminoadipate reductase (AAR) of this pathway catalyzes the conversion of α-aminoadipic acid to α-aminoadipic-δ-semialdehyde by a complex mechanism involving two gene products, Lys2p and Lys5p. The LYS2 and LYS5 genes encode, respectively, a 155-kDa inactive AAR and a 30-kDa phosphopantetheinyl transferase (PPTase) which transfers a phosphopantetheinyl group from coenzyme A (CoA) to Lys2p for the activation of Lys2p and AAR activity. In the present investigation, we have confirmed the posttranslational activation of the 150-kDa Lys2p of Candida albicans, a pathogenic yeast, in the presence of CoA and C. albicans lys2 mutant (CLD2) extract as a source of PPTase (Lys5p). The recombinant Lys2p or CLD2 mutant extract exhibited no AAR activity with or without CoA. However, the recombinant 150-kDa Lys2p, when incubated with CLD2 extract and CoA, exhibited significant AAR activity compared to that of wild-type C. albicans CAI4 extract. The PPTase in the CLD2 extract was required only for the activation of Lys2p and not for AAR reaction. Site-directed mutational analysis of G882 and S884 of the Lys2p activation domain (LGGHSI) revealed no AAR activity, indicating that these two amino acids are essential for the activation. Replacement of other amino acid residues in the domain resulted in partial or full AAR activity. These results demonstrate the posttranslational activation and the requirement of specific amino acid residues in the activation domain of the AAR of C. albicans.